Novel therapeutics in hairy cell leukemia. Issue 11 (2nd November 2019) - Sarvaria, Aditya; Saven, Alan
ABSTRACT: Introduction : Hairy Cell Leukemia (HCL) is an indolent lymphoproliferative disorder resulting in a high complete response rate when treated with purine nucleoside analogs. However, at some time, nearly all patients relapse. In the relapsed setting, historically, options beyond repeat treatment with a purine nucleoside analog were limited. A number of novel agents have now been prospectively studied clinically for HCL in this setting. Areas covered : A review of the prospective data on newer agents in the relapsed setting is discussed. Emphasis is placed on overall response rates, complete response rates, minimal residual disease rates, and toxicities. The drugs vemurafenib, moxetumumab-pasudotox, bendamustine, and ibrutinib, all of which are commercially available, are reviewed in greatest detail. Expert opinion : Despite the number of prospective studies recently published on these agents in HCL, questions remain about which agents to use, when to best utilize them, how to best dose or schedule them, and the role of combination therapy. Further clinical research is required to answer these questions and to discover other drugs effective in the treatment of relapsed HCL.